A non-destructive investigation of the skull of the small theropod dinosaur, Coelophysis rhodesiensis, using CT scans and rapid prototyping - Bristowe, Anthea; Parrott, Andrew; Hack, Jonothan; Pencharz, Mervyn; Raath, Michael (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 2004)
To solve preparation problems encountered in an exceptionally fragile skull of the small theropod dinosaur, Coelophysis rhodesiensis, CT scans were taken of the partially prepared skull, from which a three-dimensional wax model was built using a ‘reverse engineering’ rapid prototyping technique. The resulting wax model was then consulted to trace and describe cranial elements of the dinosaur that were otherwise concealed by the matrix or overlying bones, which could not be removed without risk of damage to the original fossil bone.